1993
DOI: 10.1016/1010-7940(93)90208-s
|View full text |Cite
|
Sign up to set email alerts
|

Warm body, cold heart surgery *1Clinical experience in 2817 patients

Abstract: Systemic hypothermia is used almost universally in cardiac surgery. Since 1987, 2817 patients have had normothermic cardiopulmonary bypass (NCPB, "warm body", bladder temperature 36 degrees C) with cold blood cardioplegic arrest ("cold heart", 8 degrees-14 degrees C) during open heart surgery. No patients were denied this technique regardless of age, condition or severity of surgery. Clinical Characteristics in Patients: Age range: 16-84 years, mean 66; male/female ratio 3:1; pump time (min) 24-183, mean 91; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…Similar results have been reported by several authors (23,24). In a large observational study involving 2817 patients, Singh et al (23) found no evidence of important side effects due to normothermic CPB.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results have been reported by several authors (23,24). In a large observational study involving 2817 patients, Singh et al (23) found no evidence of important side effects due to normothermic CPB.…”
Section: Discussionsupporting
confidence: 82%
“…5 The limited uncontrolled clinical data available suggest that the risks of renal failure associated with normothermic and hypothermic CPB are comparable. 6 Ip-Yam and associates 7 demonstrated no difference in creatinine clearance, fractional sodium excretion, microalbuminuria, and urinary N-acetyl-b-D-glucosaminidase (NAG) after normothermic (37 C) versus hypothermic (28 C) CPB. In a randomized controlled trial in adults, our group 8 demonstrated that CPB perfusion temperature does not influence perioperative changes in serum markers of renal function and that normothermic CPB was not associated with an increased risk of postoperative renal failure.…”
mentioning
confidence: 99%
“…However, current evidence from the introduction of normothermic perfusion, shorter intubation time and improved hemodynamic conditions has been reported and, in addition, reduced blood loss is an another interesting piece of evidence. [13][14][15][16][17] The hemostatic effect of aprotinin in addition to the benefit of normothermic perfusion was the interesting subject of the present blood conservation trial.…”
Section: Discussionmentioning
confidence: 99%